RECONSTRUCTION OF GORONTALO CUSTOMARY ECOPHILOSOPHY: CRITIQUE OF DEVELOPMENT ANTHROPOCENTRISM AND REVITALIZATION OF LOCAL WISDOM IN ECOLOGICAL DISASTER MITIGATION - Fadly Umadji; Mohamad Safaat; Usman Pakaya (Jurnal Ilmu Pendidikan dan Budaya, 2026)
The ongoing environmental crisis, characterized by an increasing frequency of hydro-meteorological disasters and massive land conversion in Gorontalo, indicates a fundamental failure of the development paradigm dominated by instrumental anthropocentrism. This ethic ontologically reduces nature to an object of exploitation, contradicting the principles of sustainability. This research aims to philosophically examine the ethical framework of Gorontalo’s indigenous wisdom as an alternative for ecological disaster mitigation and to reconstruct an ethical relationship between humans and forests. Using a qualitative method with a critical philosophical analysis approach and a comparative literature study against empirical disaster data in Gorontalo, it was found that Gorontalo’s Indigenous Environmental Philosophy is based on Theocentrism as encapsulated in the Adati Hula-hula'a To Sara'a philosophy. This concept positions humans as Khalifah (trustees) who are obligated to maintain mizan (ecological balance), rejecting the claims of absolute ownership central to Anthropocentrism. . Indigenous wisdom, such as the Molapo tradition and the Payu Limo lo Lipu principle, functionally represent a form of Practical Ecocentrism that provides moral boundaries (an ethic of self-restraint) and customary spatial regulation. The failure of disaster mitigation in Gorontalo stems from ethical decadence and the abandonment of customary authority for short-term economic interests. Therefore, this study recommends the philosophical reconstruction of regional policies by integrating the Indigenous Theocentric Ethic as the ontological basis for regulation. Revitalization of customary authority to enforce Molapo is necessary to restore the integrity of the upstream ecosystem and achieve sustainable, culturally-based disaster mitigation.